Grape moth density in Bordeaux vineyards depends on local habitat management despite effects of landscape heterogeneity on their biological control. Issue 6 (30th January 2017) - Rusch, Adrien; Delbac, Lionel; Thiéry, Denis
Summary: Biological control of crop pests is a major ecosystem service affected by several variables acting at multiple spatial scales. Among these variables, heterogeneity at the habitat and landscape scales are known key drivers of trophic interactions and pest density in agroecosystems. However, studies that try to disentangle their relative effects in perennial cropping systems are scarce and nothing is known about their impacts on insect pest density and pesticide applications. We examined the effect of heterogeneity at these two scales on grape moths, one of the most damaging insect pests in European vineyards, and their biological control in 20 vineyards during three consecutive years. We used local vegetation management and the proportion of semi‐natural habitats in the surrounding landscape as proxies of heterogeneity at the habitat and landscape scales. Grape moth density was measured over time, as well as biological control services provided by different groups: birds, invertebrate predators, parasitoids and entomopathogenic fungi. Over the 3 years, grape moth density was mainly determined by local heterogeneity, with significantly fewer larvae of the first generation established in vineyards with full compared to partial grass cover. Despite these effects, biological control of grape moths was not primarily affected by local vegetation management but by landscape heterogeneity, and the direction of this effect varied over time. Notably, predation by birds increased with landscape heterogeneity in spring, depending on local vegetation management, while attacks by pathogenic fungi decreased with landscape heterogeneity during winter. Synthesis and applications . Our results suggest that bottom‐up processes related to habitat heterogeneity drive grape moth occurrence much more than top‐down processes. These results have important implications for the ecological intensification of vineyard landscapes. We found that maintaining full grass cover within vineyards reduced grape moth density to a level below common intervention thresholds. Landscape heterogeneity in the close vicinity of vineyards contributed to improved biological pest control by birds, but depended on local vegetation management. Moreover, opposing effects of landscape management on biological pest control services over time revealed that strategies based only on manipulating landscape heterogeneity might not be the optimal option to limit grape moth density in vineyards. Abstract : Our results suggest that bottom‐up processes related to habitat heterogeneity drive grape moth occurrence much more than top‐down processes. These results have important implications for the ecological intensification of vineyard landscapes. We found that maintaining full grass cover within vineyards reduced grape moth density to a level below common intervention thresholds. Landscape heterogeneity in the close vicinity of vineyards contributed to improved biological pest control by birds, but depended on local vegetation management. Moreover, opposing effects of landscape management on biological pest control services over time revealed that strategies based only on manipulating landscape heterogeneity might not be the optimal option to limit grape moth density in vineyards.